Rekonstruksi Kebijakan CSR di Indonesia Sesuai Analisis Hukum, Implementasi, dan Arah Reformasi - Abednego Satrio Nugroho Purba; Cecep Suhardiman (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Corporate Social Responsibility (CSR) in Indonesia has undergone a paradigmatic shift from voluntary philanthropic activities to a legally binding obligation grounded in various statutory regulations, particularly Law Number 40 of 2007 on Limited Liability Companies and Law Number 25 of 2007 on Investment. This study aims to analyze the legal framework governing CSR in Indonesia from a public policy perspective, to evaluate the implementation of CSR by corporations, and to identify normative and empirical constraints that hinder the optimization of CSR as an instrument of sustainable development. The research employs a normative juridical method with statutory, conceptual, case-based, and policy analysis approaches. The findings indicate that CSR regulation remains partial in nature, primarily due to the limitation of mandatory obligations to specific sectors, the absence of clear and enforceable sanctions, and the lack of national standards for reporting and oversight.